Moral civil responsibility of Physicians from Administrative point of view: A case study on a number of Saudi hospitals - Albugami, Moteb Ayesh; Al-Qudah, Hasan Salih (Journal of Economic, Administrative and Legal Sciences, 2022)
The need for medical responsibility and to extent its relationship that can occur from physicians, as their awareness of size to error and medical responsibility that falls on them in light and existence of an effective law and legislative system in Saudi Arabia, is special to assessing the value committed to medical responsibility and the misdemeanors that are decided and evaluated, In the events of error occurring intentionally or unintentionally, the issue of medical responsibility still raises a lot of controversy due to the difficulty of linking medical sciences with administrative and legal sciences, because the field of medical work is still shrouded in a lot of confusion and ambiguity due to the complexity and accuracy of the branches of medical science. This present study seeks to shed light on the health sector, as it is supervising in issuing regulations, instructions and laws that contribute to organization and development of multiple regulations aimed at protecting the interests of country and citizen. The study concentrates in the first degree to patients who have been exposed to a medical error, with study sample of 100 individuals, and retrieved 95 questioners. The study methodology on two approaches: Descriptive method and the Field method. The study results are: 1- Increasing the number of medical teams 2- Reducing physicians assignment of additional burdens more than their actually perform as additional work they perform 3- Providing training opportunities for hospital workers to keep pace with continuous scientific development and catch up with technology to increase their ability to optimize the use of modern devices. 4- Focusing on external training courses that allow employees to exchange experiences with others. The study recommended the importance of developing team spirit within the work environment among to employees working in the hospital, to create a comfortable atmosphere, which affects the service provided to patients. And taking into account fairness and integrity in the division of work among doctors